INTERAKSI AGAMA DAN POLITIK HUKUM KESULTANAN KUTAI KARTANEGARA: Studi Keagamaan Etnis Dayak - Kutai (UINSI Samarinda, 2012)
Kutai Kingdom in the stage history of the archipelago have left traces of civilization. At least the built form of monarchy has got a touch of constitutional govern life in society. Constitutional monarchy called Panji Selaten, and Baraja Niti Law is the law that puts the combination of building indigenous aspects of egalitarianism, which is located between the Dayak and Kutai inland located near the center of power, where the top leadership is the king of Kutai. Building a constitution that remains grounded in the realm of